PdCu alloy nanodendrites with tunable composition as highly active electrocatalysts for methanol oxidation. Issue 10 (17th January 2017) - Xiong, Yaling; Ye, Wenying; Chen, Wenlong; Wu, Yiwen; Xu, Qingfeng; Yan, Yucong; Zhang, Hui; Wu, Jianbo; Yang, Deren
Abstract : PdCu alloy nanodendrites were prepared and exhibited enhanced catalytic properties towards methanol oxidation relative to commercial Pd/C. Abstract : Metal nanodendrites composed of highly branched arms have received great attention as electrocatalysts owing to their reasonably large surface area and the potential existence of low-coordinated sites in high densities. Although significant progress has been made in the synthesis of bimetallic nanodendrites, few works involve a system consisting of Pd and Cu, particularly in the case of alloyed nanodendrites. Here, we report a facile and powerful approach for the synthesis of PdCu alloy nanodendrites with tunable composition through varying the molar ratio of the Pd and Cu salt precursors. The key to achieving PdCu alloy nanodendrites is the use of W(CO)6, which serves as a strong reducing agent. In addition, variation in the molar ratio of the precursors, from Pd rich to Cu rich, leads to shape evolution of the PdCu alloy, moving from a polyhedral to a dendritic nanostructure. This result indicates that galvanic replacement between a Cu rich alloy and a Pd precursor also plays an important role in the formation of PdCu alloy nanodendrites. When used as electrocatalysts for the methanol oxidation reaction (MOR), PdCu alloy nanodendrites exhibit remarkably enhanced catalytic properties relative to commercial Pd/C. Specifically, Pd35 Cu65 alloy nanodendrites show the highest specific activity and mass activity for the MOR, 9.3 and 7.6 times higher than that of commercial Pd/C, respectively. This enhancement can be attributed to their dendritic structure and a possible bifunctional mechanism between Pd and Cu.